A Latent Transition Analysis of Youth Bullying Victimization Patterns over Time and Their Relations to Delinquency. Issue 7 (April 2022) - Zhang, Saijun; Hong, Jun Sung; Hao, Ying; Lee, Na Youn; Piquero, Alex R.
Peer victimization patterns from elementary school transitioning into late middle school have not been assessed in detail. Even less work has considered how these patterns differ across family context and then are linked to delinquency in adolescence. This study used longitudinal data ( n = 2, 892) from the Fragile Families and Child Wellbeing Study to examine peer victimization classification and change over six years while distinguishing across sex and family contexts. Latent transition analysis (LTA) shows that youth can be classified into minor victimization, mainly verbal victimization, and all-type victimization subgroups over time with some sex differences, regardless of whether they were in two-parent families. The majority of the youth were in either the mainly verbal victimization (53% for boys; 42% for girls) or all-type victimization (12% for boys; 21% for girls) statuses when they were about 9 years old, but substantial transition positioned most boys (84%) and girls (82%) in the minor victimization status instead when they were about 15 years old. Youth who were Hispanic, in two-parent families, and more open to parents had a reduced risk of peer victimization, but youth who were in a poor family had an increased risk of peer victimization. Peer victimization statuses were significantly associated with youth delinquency, and there were sex and time differences in the association. In year 9, 45% to 94% of boys and 24% to 75% of girls were involved in delinquency based on their victimization statuses, but the difference was 48% to 67% for boys and 39% to 59% for girls in year 15. The findings suggest developing and implementing peer victimization prevention starting from early elementary school, concurrently addressing peer victimization and delinquency, and paying close attention to sex and family context differences.